Internal Communication Patterns in Organizational Dynamics Within The Informal Structure of The Otaku Coffee Shop - Niken Anjelica Vernorita; Welly Wihayati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
This research discusses the dynamics of internal communication in a non-formal organization at Coffee Shop Otaku in Kuningan Regency. The main issue studied is internal communication within an organization that has a simple structure, consisting of an owner, a general manager, and staff. The purpose of this study is to identify patterns of internal communication, as well as factors that support and hinder smooth communication at Coffee Shop Otaku. The method used was descriptive qualitative with data collection techniques through in-depth interviews and observations, conducted on four informants consisting of three key informants, namely the organizational structure levels at Otaku, and one supporting informant, namely Otaku's regular customers. The results show that the communication pattern is effective, with the most dominant being a two-way vertical communication pattern, where the general manager acts as the center of the communication network. Factors that support smooth communication include a family-like culture, openness in communication, and a focus on clear objectives. However, there are several obstacles, such as unclear division of tasks and responsibilities due to the lack of a complete structure. The conclusion of this study states that although a non-formal structure can still function effectively in the early stages of organizational development, formalization of the organizational structure is still necessary to support further growth.